Medication-overuse headache: a perspective review. (August 2016) - Westergaard, Maria Lurenda; Munksgaard, Signe Bruun; Bendtsen, Lars; Jensen, Rigmor Højland
Medication-overuse headache (MOH) is a debilitating condition in which frequent and prolonged use of medication for the acute treatment of pain results in the worsening of the headache. The purpose of this paper is to review the most recent literature on MOH and discuss future avenues for research. MOH accounts for a substantial share of the global burden of disease. Prevalence is often reported as 1–2% but can be as high as 7% overall, with higher proportions among women and in those with a low socioeconomic position. Management consists of withdrawing pain medication, focusing on prophylactic and nonmedical treatments, and limiting acute symptomatic medication. Stress reduction and lifestyle interventions may support the change towards rational pain medication use. Support, follow up, and education are needed to help patients through the detoxification period. There is fertile ground for research in MOH epidemiology, pathophysiology, and neuroimaging. Randomized and long-term follow-up studies on MOH treatment protocols are needed. Further focused research could be of major importance for global health.